Diagnosis and comprehensive management of odontogenic sinusitis. A systematic review - Muñoz, Brenda (2022)
Odontogenic sinusitis has a high prevalence within the pathologies of the maxillary sinus, due to the proximity of the roots of the antral teeth to the floor of the maxillary sinus and their common vascularization. The diagnosis and treatment are parameters that have been arduously investigated, however there is no established clinical consensus on its most appropriate management. Therefore, the objective of this systematic review without meta-analysis is to develop a clinical recommendation based on available and updated evidence on the diagnosis and management of odontogenic sinusitis using the GRADE approach to determinate the certainty level for the recommendations, this will contribute to making appropriate decisions for patients with this pathology. The database examined was Medline via Pubmed using search criteria based on the PICO question including studies with a data of 10 years, the selection of studies was carried out independently by three researchers through the RAYYAN platform. The results of the 15 studies carried out showed, one study of very high quality, six of high quality, four of moderate quality, one of low quality, three of very low quality. Regarding the GRADE analysis, four recommendations for diagnosis and four for treatment, contributing to a correct management of odontogenic sinusitis. Finally, it is concluded that cone beam computed tomography is the gold standard for diagnosis and its treatment requires multidisciplinary management.